UPAYA PENINGKATAN MINAT BELAJAR SISWA DALAM PEMBELAJARAN SEJARAH MENGGUNAKAN PENDEKATAN BERDIFERENSIASI KELAS XI SMAN N 12 PEKANBARU - Winda Febiola Samosir; Suroyo; Adiva Septiara; Rizka Septiani Aulia; Sessy Masesa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by History learning in class XI 9 of SMA Negeri 12 Pekanbaru which still uses conventional learning centered on the teacher. This results in low student interest in learning History. Evidenced by the results of the questionnaire which showed a percentage value of 12.2% and included in the criteria of "a small portion" of students who are interested in learning history. The purpose of this study is to increase student interest in learning through differentiated learning. This research is a Classroom Action Research (CAR) which describes a dynamic process including aspects of planning, implementation, observation, and reflection. This study consists of 2 cycles. The data collection technique in this study was with a questionnaire. And the research instrument used a student interest questionnaire sheet. While the data analysis technique was through the process of cleaning, coding, scoring, and entering. The results of the study revealed that there was an effect of differentiated learning on student interest in learning. This can be seen from the increase in the percentage of interest in learning in the pre-cycle with a value of 12.2% to 49.82% in cycle 1 with the criteria of "almost half". And continued the percentage increase to 68.14% in cycle 2 with the criteria of "most". So it can be concluded that differentiated learning can increase students' interest in learning History.